Study of the AGT M235T polymorphism as a potential genetic marker for the development of cardiac complications in hypertensive patients (Latakia University Journal -Medical Sciences Series, 2024)
Background: Cardiovascular diseases caused by hypertension constitute a major burden on the health care system around the world, and efforts have recently focused on searching for the genetic factors that cause them. The M235T polymorphism of the angiotensinogen gene (AGT) has received much attention due to its association with  hypertension and cardiac damage in many countries. Therefore, we aimed in this study to investigate the prevalence and importance of this polymorphism in the development of heart disease in a segment of Syrian hypertensive patients.Materials and methods: This study included 40 participants of both sexes (25 of hypertensive patients with a cardiac complications and 15 healthy controls). Data were collected and the safety of the participants’ cardiovascular system was examined. DNA was extracted from blood samples using the column method. The genotyping of AGT M235T polymorphism based on PCR-RFLP. STATA was used for the statistical study.Results: After amplifying the required sequence of the AGT gene using PCR technology, we obtained a single fragment with a length of 98 bp, and after digestion using the restriction enzyme BstFNI (RFLP technology), the genotypes of the AGT M235T polymorphism were distinguished based on the length of the fragments formed as follows: MM (98 bp) , TT (77 bp), MT (98 bp and 77 bp), and the frequencies of the genotypes (TT, MT, MM) were respectively in the patient group (56%, 32%, 12%), and in the controls group (20%, 13.33%, 66.6%), and the frequency of the TT genotype in patients was five times higher than in controls, with significant statistical significance, and the frequency of the T allele in the patient group was higher than in the controls.Conclusion: The presence of the M235T polymorphism was associated with cardiac complications in patients with hypertension, and the TT genotype was the most frequent in these patients, and it can be considered as a potential genetic marker for the development of cardiovascular diseases in them.